The Influence of Electronic Word of Mouth (e-WOM) on Facebook on Purchase Decisions - Elfira Elfira; Yeye Suhaety; Dian Urna Fasihat (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to analyze the effect of Electronic Word of Mouth (e-WOM) on consumer purchasing decisions through Facebook at IKM Mart Mangge Asi in Dompu Regency. Research Method: This study employed an associative quantitative approach. The population comprised 992 Facebook followers of IKM Mart Mangge Asi, of whom 91 were selected using purposive sampling. Data were collected through a Likert-scale questionnaire. The data were analyzed using simple linear regression, supported by tests of validity, reliability, and classical assumptions. Results and Discussion: The findings show that e-WOM has a positive and significant effect on consumer purchasing decisions. However, this high value should be interpreted with caution due to potential construct proximity or measurement bias. Implications: The findings suggest that e-WOM is an important factor in digital marketing practices, particularly for small and medium-sized enterprises that use social media. Future studies are recommended to include additional variables such as brand trust, service quality, and other digital platforms. Originality: This study provides empirical evidence on the role of e-WOM in influencing consumer purchasing decisions through Facebook in the context of a local SME in Dompu Regency.